Influence of blood phenylalanine level variations on the development of executive functions and social cognition in children with phenylketonuria - Cristiane Mendes de Almeida Duarte; Flavia Balbo Piazzon; Isadora Salvador Rocco; Claudia Berlim de Mello (Elsevier, 2023)
Objective: To investigate the performance of 27 children with phenylketonuria (PKU) in tests of Executive Functions (EF) and Social Cognition (SC), and their associations with metabolic control inferred by phenylalanine (Phe) levels. Methods: The PKU group was dichotomized according to baseline Phe-levels into; ''classical PKU''(n = 14), with Phe-levels above 1200 μmol/L (> 20 mg/dL); and ''mild PKU'' (n = 13) with Phe-between 360 and 1200 μmol/L (6-20 mg/dL). The neuropsychological assessment focused on the EF and SC subtests of the NEPSY-II battery and intellectual performance. Children were compared to age-matched healthy participants. Results: Participants with PKU presented significantly lower Intellectual Quotient (IQ) compared to controls (p = 0.001). Regarding EF analysis adjusted by age and IQ, significant differences between groups were observed only in the executive attention subtests (p = 0.029). The SC set of variables was significantly different between groups (p = 0.003), as in the affective recognition task (p < 0.001). In the PKU group, the relative variation of Phe-achieved 32.1 ± 21.0%. Relative Phe-variation was correlated only with measures of Working Memory (p < 0.001), Verbal Fluency (p = 0.004), Inhibitory Control (p = 0.035) and Theory of Mind (p = 0.003). Conclusions: Phonological Verbal Fluency, Working Memory, Inhibitory Control, and Theory of Mind were shown to be most vulnerable when there is non-ideal metabolic control. Variations in the level of Phe-may have a selective negative effect on Executive Functions and Social Cognition, but not on intellectual performance.